2019
DOI: 10.3233/wor-192977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of low back disorders among waste collection workers: A systematic review

Abstract: BACKGROUND: Waste management is a growing industry worldwide. Working conditions may entail risk factors for musculoskeletal disorders, and especially low back disorders (LBD). OBJECTIVE: The purpose of this study was to perform a systematic review on: (i) the prevalence of LBD; and (ii) risk factors for LBD among waste collection workers. METHOD: A search was conducted in three electronic databases: Ovid Medline, EMBASE, and Global Health ePublications. Data were extracted on study design, sampling strategy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…12 In a study involving a one-year follow-up of disability leave due to musculoskeletal pain, those workers who had sick days due to pain and decreased over the year and people who had sick days and increased over the year all had modifiable lifestyle factors at the time they were in disability leave, such as BMI, smoking status and vigorous leisure-time physical activity. [8][9][10] There are previous systematic reviews on musculoskeletal pain in different populations like young workers, 13 dental professionals, 14 office workers, 15 waste collection workers, 16 and farmers. 17 To the author's knowledge, there is no systematic review that covers musculoskeletal pain in college students.…”
Section: Introductionmentioning
confidence: 99%
“…12 In a study involving a one-year follow-up of disability leave due to musculoskeletal pain, those workers who had sick days due to pain and decreased over the year and people who had sick days and increased over the year all had modifiable lifestyle factors at the time they were in disability leave, such as BMI, smoking status and vigorous leisure-time physical activity. [8][9][10] There are previous systematic reviews on musculoskeletal pain in different populations like young workers, 13 dental professionals, 14 office workers, 15 waste collection workers, 16 and farmers. 17 To the author's knowledge, there is no systematic review that covers musculoskeletal pain in college students.…”
Section: Introductionmentioning
confidence: 99%
“…Os processos de coleta, triagem e prensagem consistem, portanto, em atividades de prolongada permanência em pé, alto esforço físico para erguer ou arrastar grandes cargas de peso, poucas pausas para descanso e movimentos repetitivos. Essas características dos processos de trabalho também são observadas em outras cooperativas de catadores e evidenciam os riscos de adoecimento e lesão da atividade de catador (Araújo e Sato, 2018;Asante et al, 2019;Cruvinel et al, 2019). Nesse cenário, as catadoras preferem realizar a coleta do que a triagem, uma vez que o trabalho de coleta permite algumas pausas, estar ao ar livre e interagir com os moradores, além de, muitas vezes, ganharem panelas, eletrodomésticos, brinquedos e roupas dos moradores.…”
Section: Resultsunclassified
“…In 2014, about 40% of the reported occupational diseases were in the U.S. warehouses [37]. According to a review study conducted by Asante et al [38], the 12-month prevalence of LBP is between 16% and 74% in waste collection workers. A survey among freight workers in the central market of India by Gangopadhyay and Das [39] showed that they felt pain and discomfort in all parts of the body.…”
Section: Discussionmentioning
confidence: 99%